Peran Etika Kristen dalam Membentuk Keharmonisan dan Ketahanan Keluarga Berdasarkan Efesus 5:22-33 - Alfonsus Johanres Tonu Lema; Setrianto Tarrapa (Institut Agama Kristen Negeri Toraja, 2026)
Abstract: This study aims to analyse the role of Christian ethics in fostering family harmony and resilience based on Ephesians 5:22–33. The study employs a qualitative approach using literature review and a limited number of interviews with Christian families. The focus of the study is to understand how the values of love, respect, humility, and obedience taught in the Apostle Paul’s letter to the church in Ephesus are applied in modern family life. The results of the study indicate that families who consistently apply Christian ethical principles have more harmonious relationships, healthier communication, and a greater ability to deal with domestic conflicts. The values of a husband’s love for his wife, a wife’s respect for her husband, and a child’s obedience to their parents form the primary foundation for building a family that is morally and spiritually strong. This study concludes that the teachings of Christian ethics in Ephesians 5:22–33 remain relevant for application within the context of modern families as a basis for fostering family harmony and resilience. Abstrak: Penelitian ini bertujuan menganalisis peran etika Kristen dalam membentuk keharmonisan dan ketahanan keluarga berdasarkan Efesus 5:22–33. Penelitian menggunakan pendekatan kualitatif dengan metode studi pustaka. Fokus penelitian adalah memahami bagaimana nilai kasih, penghormatan, kerendahan hati, dan ketaatan yang diajarkan dalam surat Rasul Paulus kepada jemaat di Efesus diterapkan dalam kehidupan keluarga modern. Hasil penelitian menunjukkan bahwa keluarga yang menerapkan prinsip etika Kristen secara konsisten memiliki hubungan yang lebih harmonis, komunikasi yang lebih sehat, serta kemampuan yang lebih baik dalam menghadapi konflik rumah tangga. Nilai kasih suami terhadap istri, penghormatan istri kepada suami, serta ketaatan anak kepada orang tua menjadi fondasi utama terbentuknya keluarga yang kuat secara moral dan spiritual. Penelitian ini menyimpulkan bahwa ajaran etika Kristen dalam Efesus 5:22–33 tetap relevan untuk diterapkan dalam konteks keluarga modern sebagai dasar membangun keharmonisan dan ketahanan keluarga.